Modernização e repressão: os impactos da ditadura militar na Universidade Federal do Espírito Santo (1969-1974) - Pelegrine, Ayala Rodrigues Oliveira (2016)
In the scenario of the recent expansion of facilities for the historical research on the recent political past of Brazil, this research aims to contribute to the clarification of the impact of conservative and authoritarian modernization policy, implemented by the military dictatorship (1964-1985) in public universities in the country. The clipping of the analysis focuses on the period of the presidency of Emilio Garrastazu Medici (1969-1974), when the paradox of modernizing and repressive nuances of politics became even more evident. In the wake of the development project "fast and safe" national capitalism, the government of Medici materialized the University Reform, reaching the goal of tuning the universities with the demands of the desired brazilian “miracle". At the same time, anchored in authoritarian political culture and within an imagined anti-war, its management strengthened political repression as a means to facilitate the modernization, expanding the scope of "security community and information" of the military dictatorship to the interior of the universities. This research aims to understand how modernization and repression walked together and resonated specifically at the Federal University of Espírito Santo (UFES), from a critical analysis of the "official story" of the institution and the documentary collection produced by the work of the Truth Commission UFES.